A PAX-8-positive Female Urethra Adenocarcinoma: A Case Report with Diagnostic Challenges in Intestinal- Type Adenocarcinoma. (28th October 2020) - Torrez, M; Allen, R; Zhou, J
Abstract: Introduction/Objective: Female urethra adenocarcinoma (FUA) in women is extremely rare, representing 0.02% of all women's cancers and <1% of cancers in the female genitourinary tract. Intestinal-type primary adenocarcinoma of the urethra is even rarer, with only one documented case to our knowledge. Furthermore, PAX-8 immunoexpression in this entity has not been reported. Here we report an intestinal-type primary urethral adenocarcinoma that developed from inflammation-related metaplasia in urethral diverticulum with positive PAX-8 staining. Methods: Clinical chart review and microscopic examination on the lung, urethral, and vaginal wall biopsies and immunohistochemistry were performed. Results: A 64-year-old female with a 32-pack-year history of tobacco use was found to have multiple pulmonary nodules on imaging. The tumor cells were positive for CK7, CK20, SAT-B2, and PAX-8 and negative for TTF- 1/Napsin and ER. Positive PAX-8 immunoexpression raised the possibility of a gynecologic/Mullerian primary. Subsequent colonoscopy and imaging showed no evidence of colorectal or uterine tumors. The patient began having hematuria with intermittent urinary retention, and cystoscopy showed a 4 x 3 cm mass involving bladder neck circumferentially and invading into the vaginal wall. Urethral and vaginal tumor biopsies were performed. Morphologic examination of the urethral biopsy demonstrated intestinal metaplasia of squamous mucosa with transition from a mature to dysplastic phenotype where the adenocarcinoma originated from. The vaginal wall biopsy showed the same morphology. The urethral and vaginal wall biopsies showed a similar immunophenotype as the pulmonary nodule biopsy. Conclusion: FUA is a rare, aggressive tumor that occurs in Skene's glands. In our current case, however, it appeared to arise from inflammation-related metaplasia in urethral diverticulum. Another important finding of the case is the positive PAX-8 expression. Therefore in PAX-8 positive tumors, primary adenocarcinoma of lower urinary tract should be in the differential, along with gynecologic/Mullerian tumors.